Genetic Analysis of Adult-Onset Autoimmune Diabetes - Howson, Joanna M.M.; Rosinger, Silke; Smyth, Deborah J.; Boehm, Bernhard O.; Todd, John A. (Diabetes (New York, N.Y.), 2011)
In contrast with childhood-onset type 1 diabetes, the genetics of autoimmune diabetes in adults are not well understood. We have therefore investigated the genetics of diabetes diagnosed in adults positive for autoantibodies. GAD autoantibodies (GADAs), insulinoma-associated antigen-2 antibodies (IA-2As), and islet cell autoantibodies were measured at time of diagnosis. Autoantibody-positive diabetic subjects (n = 1,384) and population-based control subjects (n = 2,235) were genotyped at 20 childhood-onset type 1 diabetes loci and FCRL3, GAD2, TCF7L2, and FTO. PTPN22 (1p13.2), STAT4 (2q32.2), CTLA4 (2q33.2), HLA (6p21), IL2RA (10p15.1), INS (11p15.5), ERBB3 (12q13.2), SH2B3 (12q24.12), and CLEC16A (16p13.13) were convincingly associated with autoimmune diabetes in adults (P ≤ 0.002), with consistent directions of effect as reported for pediatric type 1 diabetes. No evidence of an HLA-DRB1*03/HLA-DRB1*04 (DR3/4) genotype effect was obtained (P = 0.55), but it remained highly predisposing (odds ratio 26.22). DR3/4 was associated with a lower age at diagnosis of disease, as was DR4 (P = 4.67 × 10(-6)) but not DR3. DR3 was associated with GADA positivity (P = 6.03 × 10(-6)) but absence of IA-2A (P = 3.22 × 10(-7)). DR4 was associated with IA-2A positivity (P = 5.45 × 10(-6)). Our results are consistent with the hypothesis that the genetics of autoimmune diabetes in adults and children are differentiated by only relatively few age-dependent genetic effects. The slower progression toward autoimmune insulin deficiency in adults is probably due to a lower genetic load overall combined with subtle variation in the HLA class II gene associations and autoreactivity.